Technical Aspects of Digitization of Cadastral Maps - Sapkota, Ram Kumar; Bhatta, Ganesh Prasad (Journal on Geoinformatics, Nepal, 2017)
Mankinds of the 21st century are seeking for qualitative matters. They can't be satisfied only with the normal service; they expect value added service i.e. qualitative service. To cope the customer's satisfaction, almost all sectors are enhancing their performance and service delivery system using the information technology. Digitization of cadastral map is very essential for providing effective, reliable and qualitative cadastral services. Having the digitized cadastral maps and GIS database we can have a lot of advantages related to storage, management, retrieval, analysis, dissemination, update as well as IT enabled effective and reliable cadastral service delivery. In the present context of being scarcity of conventional instruments, ammonia paper and other accessories, it is crucial to enroll into this process and modernize land information in order to run with time, technology and international community. Nepalese Journal on Geoinformatics -13, 2014, Page: 42-50